2013
DOI: 10.1007/s10661-013-3257-5
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamic and in situ division rates of the dominant Dinophysis species in Punic harbors of Carthage (Gulf of Tunis, South Mediterranean)

Abstract: This study investigates spatio-temporal variations of in situ division rate (μ) of two species of the genus Dinophysis. Based on a postmitotic index approach, estimates of μ from net-haul samples were compared during five daily cell cycles studies in three stations of the Punic harbors of Carthage (Gulf of Tunis). To study the annual cycle of Dinophysis spp., weekly sampling were carried out from March 2008 to June 2010. In addition, sampling over 24 h was conducted on three-cycle studies in late spring and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Previous studies have identified the megacytic zone and the dorsal megacytic bridge as reproductive stages of Dinophysis (REGUERA; GONZALEZ-GIL, 2001;REGUERA et al, 2003;GONZALEZ-GIL, 2007;AISSAOUI et al, 2013). Likewise, based on our findings from the South Atlantic Ocean, these stages are also present in the genus Ornithocercus, whose dorsal megacytic bridge showed a heavily striated pattern.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Previous studies have identified the megacytic zone and the dorsal megacytic bridge as reproductive stages of Dinophysis (REGUERA; GONZALEZ-GIL, 2001;REGUERA et al, 2003;GONZALEZ-GIL, 2007;AISSAOUI et al, 2013). Likewise, based on our findings from the South Atlantic Ocean, these stages are also present in the genus Ornithocercus, whose dorsal megacytic bridge showed a heavily striated pattern.…”
Section: Discussionsupporting
confidence: 82%
“…at different depths of the water column) changes and vary considerably among dinoflagellate species. Aissaoui et al (2013) observed higher rates in different species of Dinophysis during the fall and summer months, with proliferation occurring between 13°C and 30°C and within a salinity range of 33 to 40, which is suggestive of the broad adaptation of these species to environmental changes throughout the year. Given that our study involved only one season (the dry season), additional research is necessary to determine the potential effects of environmental changes on the reproductive cycle of Ornithocercus spp.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Blooms of Dinophysis spp. are usually associated with marked thermohaline stratification of the water column [ 10 , 38 , 39 , 40 ]. The ciliate prey of Dinophysis spp., frequently reported as Mesodinium rubrum , usually benefits from vertical water stratification as well [ 41 , 42 ], although blooms of the ciliate may also occur along horizontal thermohaline gradients in shallow estuaries [ 43 ].…”
Section: Discussionmentioning
confidence: 99%